Konsep Kebijakan Strategis Dalam Menangani Eksternalitas Ekonomi dari Covid - 19 Pada Masyarakat Rentan di Indonesia - Heri Kurniawansyah; Amrullah Amrullah; M Salahuddin; Muslim Muslim; Sri Nurhidayati (Indonesian Journal of Social Sciences and Humanities, 2020)
Externalities of Covid-19 greatly impact economic problems, especially in vulnerable communities. Therefore, the government must take action through strategic policies in dealing with this problem. The research objective is to describe and find out the concept of strategic policy in dealing with economic externalities of the Covid-19 pandemic in Indonesia. The method used in this research is a descriptive method, with a focus on studies of the economic externalities of Covid-19, especially in vulnerable communities, along with policies implemented by the government. While the data collection strategy is by mapping issues, mapping policies, and finding mapping strategies. Based on the systematic and the problem, the authors formulated three strategic policies, namely allocation policy, distribution policy and stabilization policy as a systematic policy in dealing with the economic impact of the Covid-19 pandemic that occurred in Indonesia.